Directing Vanillin Production From Ferulic Acid by Increased Acetyl-CoA Consumption in Recombinant Escherichia coli - Lee, E.; Yoon, S.; Das, A.; Lee, S.; Li, C.; Kim, J.; Choi, M.; Choi, M.; Kim, S.
The amplification of gltA gene encoding citrate synthase of TCA cycle was required for the efficient conversion of acetyl-CoA, generated during vanillin production from ferulic acid, to CoA, which is essential for vanillin production. Vanillin of 1.98 g/L was produced from the E. coli DH5a (pTAHEF-gltA)with gltA amplification in 48 h of culture at 3.0 g/L of ferulic acid, which was about twofold higher than the vanillin production of 0.91 g/L obtained by the E. coli DH5a (pTAHEF)without gltA amplification. The icdA gene encoding isocitrate dehydrogenase of TCA cycle was deleted to make the vanillin producing E. coli utilize glyoxylate bypass which enables more efficient conversion of acetyl-CoA to CoA in comparison with TCA cycle. The production of vanillin by the icdA null mutant of E. coli BW25113 harboring pTAHEF was enhanced by 2.6 times. The gltA amplification of the glyoxylate bypass in the icdA null mutant remarkably increased the production rate of vanillin with a little increase in the amount of vanillin production. The real synergistic effect of gltA amplification and icdA deletion was observed with use of XAD-2 resin reducing the toxicity of vanillin produced during culture. Vanillin of 5.14 g/L was produced in 24 h of the culture with molar conversion yield of 86.6